Analisis Potensi dan Efektivitas Pemungutan Pajak Restoran Terhadap Realisasi Penerimaan Pajak Restoran Di Kecamatan Kuta Selatan - Indah Anggreni, Ni Luh Putu; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi, 2020)
The purpose of this  study was to determine how much the potential and effectiveness of restaurant tax collection in the District of South Kuta. This research has been conducted in various  restaurants  located in South Kuta. The number of samples is 94 restaurants, 14 restaurants, and 4 bars, with probability sampling methods, especially Simple Random Sampling. Data collection is done through surveys, non-participant observation, and questionnaires. The analysis technique  used is quantitative descriptive. The analysis shows that the restaurant tax potential in South Kuta District in 2019 is quite large when compared to the realization and target of restaurant tax. The effectiveness of restaurant tax collection in South Kuta District in 2018 which resulted in 108 percent with very effective criteria. Keywords: Potency; Effectiveness; Realization of Revenue.